Evidence of Range Shifts in Riparian Plant Assemblages in Response to Multidecadal Streamflow Declines - White, Helen A.; Scott, John K.; Didham, Raphael K. (Frontiers in Ecology and Evolution, 2021)
Riparian corridors are thought to form hydrological refugia that may buffer species and communities against regional climate changes. In regions facing a warming and drying climate, however, the hydrological regime driving riparian communities is also under threat. We examined recruitment in response to streamflow declines for species inhabiting the riparian zone in southwest Western Australia, testing the extent to which the riparian system has buffered riparian communities from the drying climate. We stratified 49 vegetation transects across the >600 mm per annum regional rainfall gradient encompassed by the Warren River Catchment. Local hydrological conditions were estimated over two 10-year periods; 1980 to 1989, and 2001 to 2010, to quantify changes in the flood regime. Mixed effects models tested the relationship between rainfall and flooding on the proportion of immature to mature individuals of 17 species of trees and shrubs common to the riparian zones. At the low-rainfall extent of their geographic range, the proportion of immature riparian species decreased with declining flow, whereas at the high-rainfall extent of their geographic range the proportion of immature individuals increased with declining flow. These results suggest that the geographic ranges of riparian species may be contracting at the low-rainfall margin of their range, while at the high-rainfall margin of their geographic range, reduced flooding regimes appear to be opening up new habitat suitable for recruitment and narrowing the river corridor. No such patterns were observed in upland species, suggesting the river may be buffering upland species. We discuss these findings and their implications for ongoing management and species conservation in a region projected to face further, significant rainfall declines.